2003
DOI: 10.1007/s00261-003-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

CT of small bowel ischemia

Abstract: We evaluated the computed tomographic (CT) features of small bowel (SB) ischemia and necrosis and correlated the findings with clinical outcome or patient prognosis. Sixty-eight surgically or angiographically proved cases of SB ischemia were retrospectively reviewed. The CT features of intestinal ischemia were divided into three groups: (A) thinned bowel wall with poor enhancement, intramural gas, or portal venous gas; (B) thickened SB wall without superior mesenteric vein thrombosis; and (C) thickened SB wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 11 publications
1
57
0
2
Order By: Relevance
“…CT and magnetic resonance (MR) angiography are more sensitive techniques than Doppler imaging with respect to assessment of the extent of the thrombus within the portal venous system [56][57][58] . Definitive diagnosis of PVT can be obtained by MR imaging (MRI) and CT; the former provides a better evaluation of the extent of the thrombosis, particularly in the mesenteric vein, reaching a sensitivity and specificity of 98%-100%.…”
Section: Diagnosismentioning
confidence: 99%
“…CT and magnetic resonance (MR) angiography are more sensitive techniques than Doppler imaging with respect to assessment of the extent of the thrombus within the portal venous system [56][57][58] . Definitive diagnosis of PVT can be obtained by MR imaging (MRI) and CT; the former provides a better evaluation of the extent of the thrombosis, particularly in the mesenteric vein, reaching a sensitivity and specificity of 98%-100%.…”
Section: Diagnosismentioning
confidence: 99%
“…However, the development of MDCT has greatly improved the Bleeding complications (due to anticoagulation) 6 Relaparotomy 4 Others (ascites, disorientation) 5 *Some patients had more than one complication sensitivity so that it is now greater than 90 % [13,14]. A CT scan of the abdomen is now the imaging study of choice for mesenteric ischaemia, because it is rapid, non-invasive, and widely available in most hospitals and provides specific information on the location of the occluded vessel and the presence of bowel ischaemia [15] by showing bowel wall thickening, mucosal enhancement, intramural air, dilatation, portal venous gas and pneumatosis [16][17][18]. Kirkpatrick and colleagues [13] suggested that CT angiography findings of portal venous gas, pneumatosis, or a combination of bowel wall thickening with venous thrombosis, solid organ infarction, or focal lack of enhancement of bowel wall to be criteria for the diagnosis of mesenteric ischaemia; with sensitivity and specificity rates of 96 % and 94 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced enhancement is also associated with infarction 46 . In cases of incomplete arterial occlusion, arterial occlusion with reperfusion and other causes of intestinal ischemia, increased bowel wall enhancement is more commonly evident.…”
Section: Abnormal Wall Enhancementmentioning
confidence: 99%